Effect of Diabetes Self Management Education on Blood Sugar Level Control for Diabetics in Padangsidimpuan City - Adi Antoni; Eva Decroli; Afriwardi; Irwan Prayitno; Nur Indrawati Lipoeto; Nursyirwan Efendi; Hardisman (Migration Letters, 2023)
Diabetes mellitus (DM) is a chronic disease whose number is always increasing every year in the world. DM requires serious treatment in order to reduce the complications of this disease. The purpose of this study was to determine the effect of diabetes self-management education on controlling blood sugar levels in diabetics in the city of Padangsidimpuan. This study used a one group pretest-posttest only design involving 40 respondents based on sample size calculation using sample size determination in health studies. The sample technique uses proportional random sampling. The sample criteria are type 2 diabetes mellitus, diabetic patients who do not experience cognitive impairment, can communicate verbally and nonverbally. Measuring blood sugar levels using HbA1c. The results of this study indicate that the average before the DSME intervention obtained an HBA1c value of 8.828% (SD=.17725) and the average after the DSME intervention obtained an HBA1c value of 7.940% (1.1502) (p value = <0.001). DSME is effective in reducing HBA1c values in people with diabetes mellitus. So it is hoped that DM sufferers can take advantage of DSME as an independent intervention that can be done at home to prevent various problems from DM.